An overview for food loss and waste reduction in food supply chains - Ekren, Banu Y.; Kumar, Vikas (Emerald, 2022)
Creating systems designs by considering a balance between economic, environmental and social effects is significant in today’s sustainability concern. Sustainability has become an emerging topic, growing concerns and attention for companies. Especially companies operating on a global scale aim to develop strategies for sustainable supply chain management. When the supply chain is a food chain, that concern increases exponentially and sustainable management of the chain becomes a critical challenge requiring the development and implementation of innovative practices by all stages within value chains. According to the Food and Agriculture Organization (FAO) one-third of all food produced in the world is lost or wasted from farm to fork. This waste has great negative impact on global economy, food availability, as well as environment. In this work, we focus on food loss and waste subject by searching how they could be reduced in throughout a supply chain network. We provide solution ways for the food waste/loss reduction obtained from current works in literature.